2012
DOI: 10.1186/1471-2474-13-69
|View full text |Cite
|
Sign up to set email alerts
|

Engaging consumers living in remote areas of Western Australia in the self-management of back pain: a prospective cohort study

Abstract: BackgroundIn Western Australia (WA), health policy recommends encouraging the use of active self-management strategies as part of the co-care of consumers with persistent low back pain (LBP). As many areas in WA are geographically isolated and health services are limited, implementing this policy into practice is critical if health outcomes for consumers living in geographically-isolated areas are to be improved.MethodsIn this prospective cohort study, 51 consumers (mean (SD) age 62.3 (±15.1) years) participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts. 24 In this regard, long-term sustainability and impact of MoCs will be dependent on their uptake and support by middle and senior health managers and policy makers and research providing evidence of their benefit for improving health outcomes and system efficiencies.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts. 24 In this regard, long-term sustainability and impact of MoCs will be dependent on their uptake and support by middle and senior health managers and policy makers and research providing evidence of their benefit for improving health outcomes and system efficiencies.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Relationships between self-care patterns and socioeconomic and disease characteristics have been examined in previous studies,7, 8, 9 but surveys comparing more than one country are scarce 10 . However, to our knowledge, no previous studies have assessed self-care patterns in individuals actively engaged in self-care, who are most likely to practice self-care in the future.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of self-care in previous studies varied from that of a broad range of activities undertaken by laypeople as part of their health management 9 to that of specific self-care activities practiced without doctor involvement, 10 often only when experiencing symptoms 11 . To assess the self-care market, we defined self-care as the practice of self-determined home healthcare activities using appropriate products.…”
Section: Introductionmentioning
confidence: 99%
“…Back pain beliefs are known to be affected by factors such as culture, education, health literacy, place of work, personal experience of LBP and the sequelae of LBP such as disability [24,35-38]. For HCPs, the organizational and professional settings, experience in clinical practice and educational history are important correlates, some of which are potentially modifiable [39,40].…”
Section: Introductionmentioning
confidence: 99%